KEABSAHAN LARANGAN MENIKAH PADA PEKERJA KONTRAK DITINJAU DARI HUKUM POSITIF DI INDONESIA - Rahmansyah, Fahril Adi; Afifah, Wiwik (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Marriage is a constitutional right owned by each person. The prohibition to marry as stated in the work agreement has positive and negative impacts on both employers and workers. With the qualifications regarding the prohibition on marriage given by the employer, it conflicts with the personal rights of workers, especially for contract workers or workers with PKWT status. Prohibition of marriage in work agreements made is the result of agreements made by employers and workers in unequal positions because workers need decent work to fulfill their daily needs. This study aims to find out about the validity of the rules prohibiting marriage for PKWT workers contained in the work agreement. This study uses a normative juridical method that uses primary legal materials in the form of legislation and secondary legal materials. The results of the study show that what is experienced by workers and employers in their daily lives often creates differences in interests that are quite serious so that the resolution also has the effect of experiencing differences between employers and workers. Work agreements that prohibit marriage remain valid according to the Civil Code. However, the agreements made are not based on the equal or weaker position of workers compared to the employer. The right to marry is a right that can be waived because workers prioritize the right to get a decent job, decent wages to meet basic needs. However, marriage should not be prohibited and employers should provide other options as a solution so that both workers and employers get their rights